BATAS BATAS TANGGUNG JAWAB HUKUM PEJABAT PEMBUAT KOMITMEN TERHADAP KERUGIAN NEGARA DALAM PENGADAAN BARANG / JASA OLEH PEMERINTAH PRINSIP ASAS MASLAHAT - Pradipta, Radian Yudha (Jurisdictie: Jurnal Hukum dan Syariah, 2017)
Procurement involves huge State money. PPK is a party who has authority in carrying out the procurement of goods. Should there be any irregularities that cause material losses to the State’s finances to be the responsibility of PPK. Article 11 of Perpres No. 4 of 2015 concerning Procurement of Goods / Services The Government in selecting PPK must meet the requirements of either integrity, managerial or competence. This research is a normative research with literature study. The result of this study is that although the limits of the PPK’s legal liability to State Losses in Procurement of Government Goods / Services are not explicitly regulated in Presidential Decree No.4 of 2015 on Procurement of Government Goods / Services, but from several articles, especially in Article 11 , Article 12, Article 13 and Article 122 regulating PPK in the event of a State Loss in Procurement of Government Goods / Services. In the event that PPK committed unlawful conduct in its exercise of authority, the CO shall assume responsibility in accordance with the legal liability of PPK for the State Loss from the legal aspects of State administration, civil law and criminal law.